FUZZY AHP TO PRIORITIZE STRATEGY FOR SOCIAL ENTERPRISES’ SUSTAINABILITY - Desiana, Putri Mega; Maarif, M. Syamsul; Puspitawati, Herien; Rachmawati, Riani (Journal of Environmental Science and Sustainable Development, 2022)
Social Enterprise (SE) is an exciting phenomenon. Many SEs carry out activities that might be avoided by ordinary businesses pursuing profit but instead become the main targets of SE activities that have a social mission. Thus, building SE sustainability is more difficult because the problems are complex, and most SE is MSME with resource constraints. SE should be able to pick the best strategies, considering their limited resources and changing demand from the ecosystem. This research aims to formulate the priority strategies for SE sustainability. This research employs both qualitative and quantitative research methods. Three key factors and ten elements for the sustainability of SE were derived from the literature study, survey findings, and interviews with SE experts and SE players. Using the Fuzzy AHP method, the choice of strategies is combined with the opinions of experts based on existing factors. The findings are as follows. The top four strategy ranks are innovation, collaboration, and adaptive to the changing needs of society and leveraging their resources. Therefore, this research concludes that innovation should be the priority to achieve the sustainability of SE. The primary strategy must be carried out is collaborative innovation to respond to changing social needs.